Membangun Identitas Melayu Lewat Pendidikan Keparawisataan di Pulau Penyengat, Kota Tanjungpinang - Dailami .; Moh. Thandzir; Natal Olotua Sipayung; Rezki Alhamdi; Siska Amelia Maldin; Haufi Sukmamedian; Tito Pratama; Syalendra Reza Irwansyah Rezeki; Muhammad Rhomadani (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
The problem in this study is the development of tourism on Penyengat Island which has the potential to reduce the value and identity of Malay culture due to the influence of modernization and foreign culture. In addition, Malay culture-based tourism education is still not optimal in introducing local historical, customary, and cultural values to the community and tourists. Therefore, efforts are needed through tourism education to build and maintain Malay identity in the region. This research aims to analyze how tourism education plays a role in building Malay identity on Penyengat Island, Tanjungpinang. The problem in this study arises due to the development of modern tourism which has the potential to reduce local cultural values if it is not balanced with efforts to preserve Malay culture. Therefore, tourism education is considered important as a means to maintain the cultural identity of the local community while increasing awareness of the importance of preserving Malay cultural heritage. This study uses a qualitative method with a descriptive approach. Data collection techniques are carried out through observation, in-depth interviews, and documentation. The research informants were selected using purposive sampling techniques, namely traditional leaders, local communities, tourism managers, and parties involved in tourism activities on Penyengat Island. The data analysis technique uses the Miles and Huberman model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that tourism education has an important role in strengthening Malay identity through the introduction of local history, culture, customs, languages, and values to the community and tourists. In addition, community involvement in cultural tourism activities also supports the preservation of Malay identity on Penyengat Island.